(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India is an important centre of paddy. The paddy is cultivated on the largest areas in India. Historians believe that while the Indica variety of paddy was first domesticated in the area covering the foothills of the Eastern Himalayas (i.e., north-eastern India), stretching through Bunna, Thailand, Laos, Vietnam and Southern China, the japonica variety was domesticated from wild paddy in southern China which was introduced to India. Nagapattinam district in Tamilnadu was purposively selected because of majority of the farmers, farm women and agricultural labourers are directly or indirectly involved in rice crop cultivation which forms the basis for the agrarian economy of Nagapattinam district. Nagapattinam district has eight taluks. Paddy is being grown in all eight taluks. The Eight taluks are Sirkali, Nagapattinam, Mayiladuthurai, Vedaranyam, Tharangambadi, Kilvelur, Kuthalam, Thirukkuvalai. Mayiladuthurai taluk was randomly selected for the study. Six villages namely Kiloy, Manalmedu, Mudigandanallur, Kesingan, Attur, Kadalangudi were selected for the study. Sample size of 120 respondents was selected by using proportionate random sampling technique. Most of the respondents expressed labour scarcity (80.83 per cent) as the major physical constraint followed by (78.33 per cent) expressed weak extension service as a major communication constraint, lack of knowledge to identify the bio-agents (90.00 per cent) was the foremost personal constraint and Lack of credit facilities (93.33 per cent) was the major socio-economic constraint in the adoption of INM technologies in paddy cultivation.